REKONSTRUKSI HUTAN KAWASAN KARST GUNUNGSEWU DAERAH ISTIMEWA YOGYAKARTA, INDONESIA - , Lies Rahayu Wijayanti Faida, Ir.,MP. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research was carried out to seek evidence of the presence of karst forest in Gunungsewu in the past, by way of reconstructing the ancient forest. There are three objectives in this research, namely (1) to identify the history of the flora that inhabit the forests in Gunungsewu karst region, (2) to investigate the anthropogenic factors that influence changes in the type of flora in the Region, and (3) to reconstruct the spatio-temporal forest profiles in the area. Paleoecobotany approach was used as the basis for the reconstruction of forest, which is based on the law of uniformity and analogy approach. Pollen analysis and radiocarbon dating are tools to reconstruct the forest during the human cultural history in the Holocene. Data acquisition and associative comparatively analyze to obtain answers causative, so the inductive conference can be stretched about the condition of forest in the past. Age of pollen deposition layer is expressed by BP (Before the Present).Statement of age by BP is commonly used in studying the history of the earth, and is internationally adopted in 1950 as a starting point/point zero. To learn the history of human culture used scale Before Christ-Anno Domini/BC-AD, which is based on the birth of Crist as a starting point or zero point in the Gregorian calendar. Research allowed that there are three types of flora from Prehistoric times to the present, that is lower montane rain-forest of 16,894Â±440 â 9,296Â±140 years BP, tropical rainforest at 9,296Â±140â1,753Â±90 years BP, and monsoon in 1,753Â±90 years BP until now. The Euphorbiaceae was the oldest flora occupied the Region, existed between 16,894Â±440 years BP until now. While the Moraceae which known as the karst floral identity began to be found since 9,296Â±140 years BP. Prehistoric human occupation in the Gunungsewu karst area not affect the condition of flora. Cultural traits of prehistoric subsistence and territorial can explain that it is not anthropogenic factors that cause change in the types of flora, but due to climate change. Human influence on the forest decline in Islamic Empire and Colonialism which have known tenure systems even of migration and exploitation of teak by Japan that trigger changes in forest vegetation, but the loss of forest exactly happened after freedom due to the subsistence activities. Reconstruction of forest profiles in human prehistory provide information that once inhabited the lower montane rain-forest on Keplek period, then the period of Ngrijangan inhabited by a mixed type of lower montane rain-forest and tropical rain-forest. In the period of Klepu, the forest type turn into the type of tropical rain-forest. Monsoon type were residents at the type of history, since the Hinduism and Buddhism period up to the present.